ANALYSING THEDIFFERENT OF PHYSICAL ENVIRONMENT BETWEEN LION AIRAND CITILINK. A STUDY OF CUSTOMER IN MANADO - Soekamto, Militia Ch. V.; Lapian, Joyce S.L.H.V.; Wangke, Shinta J.C. (Universitas Sam Ratulangi, 2019)
Abstract: There is an increasing competition among the Air transportation in Manado. As one of the Airplane provider, Citilink and Lion Air is forced to keep they customer. Physical Environment is a very important part of a business air transportation. Due to the fact that to find new customer is much more costly rather than to retain the existing one they need maintaining and change on physical environment such as Spatiality in-flight, Amenity in-flight and Aesthetics inflight. Physical environment play a part in building customer revisit feeling safety and comfy experience In order for Airlines to be able to keep its customer, this study aims to analyze whether there is a significant difference in physical Environment between its Citilink customer and Lion Air customer, for later be used to form the best strategy. This research is a comparative research, which the data is obtained through questionnaire, and the data is analyzed using the Independent Sample t-Test. The population of this research is the customer of airlines users in Manado, with 50 respondents of Citilink customer and 50 respondent of Lion Air customer as the sample. The result shows that there is a no significant difference in physical environment. However, according to the result based on the indicators show that, there are actually no a significant difference, but with the mean value of the Citilink customer is higher than the Lion Air customer.Â Keywords: physical environment, spatiality, aesthetics, amenity, airlines